Proposta de modelo de negócio com estratégias de inovação para empresas de micro e pequeno porte : baseada em estudo realizado em empresas do segmento de moda dos municípios de Goiânia, Pontalina e Taquaral de Goiás-GO - Corsatto, Cássia Aparecida (2016)
This thesis aimed to elaborate a proposal of a business model with strategies´ innovation for micro and small companies, researching companies of the fashion segment located in Goiânia, Pontalina and Taquaral de Goiás-GO, for the facing the current competitive market. The research was motivated by the observation and experience of the difficulties presented by companies in the industrial segment, particularly those in the fashion segment, to understand the context of innovation, identify their occurrences in internal (operational) and external (strategic) factors and to integrate them to the practices of business management. In addition, mainly, to use them for the development and definition of innovation strategies as mechanisms of competitive advantage and insertion in the market. Looking this perspective and considering the globalized world, where micro and small Brazilian business are inserted which has been causing intense transformations in the business environment and which has led companies from all over the world to reconfigure themselves and seek ways to foster competitiveness, we have sought to analyze the innovation with a systemic and integrated way to the strategies and models of management of the companies evaluating the performance of the strategic and operational factors, observing its structural aspects, processes, products, commercialization competitiveness and socioeconomic sustainability among others. The information was raise through a questionnaire application that allowed characterizing the occurrences of innovation in the operational and strategic factors of the companies surveyed. Considering this, sought observe the learning and knowledge factors that stimulate the innovative processes and presenting a business model proposal with innovation strategies for micro and small business, taking into account the requirements of the importance, significance and relevance of innovation for these enterprise. In this way, it tried to establish the adherence between the business practice and the academic knowledge, establishing the relationship between the innovation, looking for to integrate to the strategies and models of management of the companies. It also sough associated it with the concepts and theoretical studies obtained through a bibliographical, theoretical and conceptual review on the themes of innovation, strategy, competitiveness, business model and micro and small enterprises. It was an empirical research, of an exploratory descriptive nature, of an applied nature, with quantitative approach insofar as it observed numerical and qualitative aspects, insofar as it collected information through individual interviews. The data collection was carry out with 45 companies from the fashion segment of Goiânia, Pontalina and Taquaral de Goiás-GO. It was take through a structured questionnaire applying in-depth interviews, the data were process and analyzed using the Survey Win 4.0, and the Excel software is resulting in the characterization of the operational and strategic factors that allowed the presentation of the business model proposal with innovation strategies. This research will contribute to promove some reflection and to improve the understanding of elements that can compose the innovation strategies aimed at micro and small companies.